GOVERNMENT COLLABORATION IN BELU REGENCY IN IMPROVING INSTITUTIONAL CAPACITY OF THE LAND BORDER AREA REPUBLIC OF INDONESIA – THE DEMOCRATIC REPUBLIC OF TIMOR LESTE - Agus Winarna; Tjahja Supriatna; Sadu Wasistiono; Dewi Sulistyani (Bajang Institute, 2022)
After the referendum of the Democratic Republic of Timor Leste, various problems arose at the border with the Republic of Indonesia. So far, efforts have been made to resolve the problems that arise at the border, but have not been fully resolved properly, in this article the focus is on the issue of institutional capacity. The method used is descriptive qualitative crisis phenomenology, then it is done through observation, interviews, documentation with triangulation techniques. The data obtained is then analyzed, through the theoretical framework used, namely the pattern of collaboration relations between the Government - Private (Private - Public Partnership), Internal Government Collaboration (Internal Government Collaboration) and multi-actor collaboration (Multi - Actor Collaboration). The results show that government collaboration in border area management has an impact on increasing community welfare and border area security. The results of the study also confirm that the pattern of collaborative relations that occurs in border area management is a collaboration model between stakeholders, involving elements of the community and the private sector in overcoming problems that occur in the land border area of ​​Belu Regency, with a theoretical synthesis to produce a Collaboration Management System Model (Collaboration Management). Model on Land Borders System, CMMBS), namely the synergy between the two models. The first model is about welfare management by the NTT provincial government as the Center of Grafity assisted by the Belu Regency Government in the Collaboration Management Model on Border Prosperity (CMMBP), while the second model is about border security management by the 161/WS Military Resort Command as the Border Security Operations Executing Command as the Center of Grafity assisted by the Border Security Task Force in the Collaboration Management Model on land Borders Security (CMMLBS). The two approaches are carried out in tandem with the relevant Ministries/Institutions, elements of the community, universities, the business/private sector, the media and other stakeholders and are supported by increased institutional capacity by the Regional Government.